2014
DOI: 10.29252/ijn.27.88.22
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Organizational Justice, Work Engagement and Positive Organizational Behavior of Nurses via Mediation of their Personal Career Goals

Abstract: Background & Aim: Each group of staff has their individual career goals in work place. The aim of the study was to determinate mediational role of personal career goals attainment in relation to organizational justice, work engagement and positive organizational behavior. Material & Methods: It was a correlational study. The statistical population was all female nurses working in Isfahan Alzahra hospital in 2013. Among them 208 nurses were recruited by stratified proportion to size random sampling method. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Organizational justice is found to be a key factor of many organizational outcome variables, such as trust, commitment, job satisfaction, organizational citizen behavior, job performance, and POB (Alexander and Ruderman, 1987 ; Moorman, 1991 ; McFarlin and Sweeney, 1992 ; Cohen-Charash and Spector, 2001 ; Colquitt et al, 2001 ; Wong et al, 2006 ; Karriker and Williams, 2009 ; Zainalipour et al, 2010 ; Keyvanar et al, 2014 ; Khan et al, 2016 ; Nastiezaie and Jenaabadi, 2016 ). For instance, Alexander and Ruderman ( 1987 ) suggested that all fairness variables, as a group, are significantly associated with employees' work-related attitudes and behaviors and procedural fairness and distributive fairness have distinct effects on the organizational outcomes.…”
Section: The Theoretical Background and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational justice is found to be a key factor of many organizational outcome variables, such as trust, commitment, job satisfaction, organizational citizen behavior, job performance, and POB (Alexander and Ruderman, 1987 ; Moorman, 1991 ; McFarlin and Sweeney, 1992 ; Cohen-Charash and Spector, 2001 ; Colquitt et al, 2001 ; Wong et al, 2006 ; Karriker and Williams, 2009 ; Zainalipour et al, 2010 ; Keyvanar et al, 2014 ; Khan et al, 2016 ; Nastiezaie and Jenaabadi, 2016 ). For instance, Alexander and Ruderman ( 1987 ) suggested that all fairness variables, as a group, are significantly associated with employees' work-related attitudes and behaviors and procedural fairness and distributive fairness have distinct effects on the organizational outcomes.…”
Section: The Theoretical Background and Hypothesismentioning
confidence: 99%
“…For instance, Alexander and Ruderman ( 1987 ) suggested that all fairness variables, as a group, are significantly associated with employees' work-related attitudes and behaviors and procedural fairness and distributive fairness have distinct effects on the organizational outcomes. Keyvanar et al ( 2014 ) studied organizational justice and POB in the context of hospital and found that organizational justice is related to POB (hope, optimism, self-efficacy, and resiliency) and work engagement through the attainment of personal career goals. Nastiezaie and Jenaabadi ( 2016 ) showed that organizational justice has a significant and positive correlation with POB A small number of researches explored how perceptions of fair treatment influence the employee's beneficial behavior.…”
Section: The Theoretical Background and Hypothesismentioning
confidence: 99%
“…Also, in Shahid Sadough Hospital in Yazd, Iran, it was observed that there is a significant relationship between organisational behaviour and the hospital productivity even though, the employee behaviour is said to be improved when there is any policy that brings about a better organisational justice perception and in return increases health sector outcome (Bahrami et al, 2014). Corroborating behaviour being influenced by perceived organisational justice is the work of (Keyvanar et al, 2014). They opined that organisational justice is positively related to organisational behaviour, thereby encouraging whatever will foster OCB amidst the nurses in the hospital establishment.…”
Section: Conceptual Frameworkmentioning
confidence: 99%